Simulations of the effect of particle size on texture and force transmission in bidisperse granular composites - Itthichai Preechawuttipong (2018)
© The Authors, published by EDP Sciences, 2017. The objective of this study is to investigate the influence of the particle size ratio on texture and force transmission in two-dimensional cohesionless binary granular composties by using molecular dynamics (MD) simulations. Four numerical composite samples, which differ in terms of the particle size ratios, are used in this study. The samples are composed of two constitutive materials with a stiffness ratio of four between the higher one termed as stiff particle and another termed as soft particle. The samples are subjected to an uniaxial confined vertical compression on the upper wall. The results under static conditions show that the particle size ratio mainly affects the contact sub-networks. The coordination number decreases when the particle size ratios (Dstiff/Dsoft = 1.2-3.0) increase, contrary to stiff-any case. Considering the spatial arrangement of contact directions, contacts between stiff particles exhibit an anisotropic distribution. On the contrary, the other contacts, i.e. soft-soft and stiff-soft contacts play a role to support the granular system in equilibrium. It is interesting to note that for all the particle size ratios, an exponential distribution and power-law are observed for the strong and weak network, respectively. Furthermore, almost 60% of the entire contacts transmit the weak forces.